(untitled) (Bangladesh Journal of Medical Biochemistry, 2014)
Majority of the patients with end stage renal disease (ESRD) are on maintenance hemodialysis (MHD) in Bangladesh. Dialysis patients are at high risk for contracting blood borne infection including hepatitis C virus (HCV) infection. The aim of this study was to evaluate the antibody response of hepatitis C virus infection in patients on MHD by detecting different viral markers in blood. A total of 88 patients with chronic kidney disease (CKD)were recruited from BIRDEM and BSMMU during the period from June 2006 to June 2007. Of them 63 patients on MHD and 25 predialysis patients were taken as cases and controls respectivly. Anti-HCV antibody were positive in 38% of dialysis patients but none of the controls were positive for Anti-HCV. When HCV positive MHD patients (38%) were compared to HCV negative MHD patients (62%), it showed that HCV positive patients had longer duration of dialysis (24±25 vs 9±6 months, p<0.001), increased number blood transfusions (29±34 vs 10±9 units, p<0.004) and elevated serum alanine aminotransferase level (35±23 vs 20±9 U/L, p=0.001). Implementing comprehensive infection control program by routine screening of the CKD patients, safe blood transfusion program, reducing transfusion of blood by use of erythropoietin and proper disinfection and cleaning of hemodialysis units may reduce the infection by HCV Virus. DOI: http://dx.doi.org/10.3329/bjmb.v7i1.18573 Bangladesh J Med Biochem 2014; 7(1): 9-13